The influence of self-efficacy and outcome expectations on the relationship between perceived environment and physical activity in the workplace - Plotnikoff Ronald C; Prodaniuk Tricia R; Spence John C; Wilson Phillip M (BMC, 2004)
Abstract Background Recent research and commentary contends that ecological approaches may be particularly useful for understanding and promoting physical activity participation in various settings including the workplace. Yet within the physical activity domain there is a lack of understanding of how ecological environment factors influence behaviour. Thus, the purpose of this study was to examine the relationships between perceived environment, social-cognitive variables, and physical activity behaviour. Methods Participants (N = 897) were employees from three large worksites who completed self-report inventories containing measures of self-efficacy, outcome expectations, perceptions of the workplace environment (PWES), and physical activity behaviour during both leisure-time and incorporated throughout the workday. Results Results of both bivariate and multiple regression analyses indicated the global PWES scores had a limited association with leisure-time physical activity (R2adj =.01). Sequential regression analyses supported a weak association between physical activity incorporated in the workplace and PWES (R2adj = .04) and the partial mediation of self-efficacy on the relationship between PWES and workplace physical activity (variance accounted for reduced to R2adj = .02 when self-efficacy was controlled). Conclusion Overall, the results of the present investigation indicate that self-efficacy acted as a partial mediator of the relationship between perceived environment and workplace physical activity participation. Implications of the findings for physical activity promotion using ecological-based approaches, and future directions for research from this perspective in worksite settings are discussed.